Persepsi Guru Dan Dosen Tentang Homestay Dalam Melakukan Kegiatan Wisata Edukasi Sekolah - Ratu Bilqis, Linda Desafitri; Irfal, Irfal; Mustika, Amalia (Jurnal Ilmiah Pariwisata, 2021)
Educational tourism can be a means of socializing and fostering a sense of pride and love for culture and the nation where tourism activities are carried out by visitors and are primarily aimed at obtaining education and learning. In conducting educational tours, accommodation is needed, one of which is a Homestay. The purpose is to determine the perceptions of teachers and lecturers about Homestays as an alternative accommodation for educational tours. The research method is descriptive quantitative method which was conducted on 100 respondents consisting of junior high school, vocational / high school teachers and university lecturers in Jakarta using quota sampling. The conclusion of this study is that the perception with motives prefers living in a Homestay because the price is relatively cheaper in conducting educational tours and it is recommended that Homestay owners can offer more than 1 (one) room or room so that more accommodating students or students who will stay in the tourist village area and for teachers and lecturers to keep choosing Homestay as a place to stay for their students or students for educational activities, in order to help government programs to improve the economy of local residents in a tourist village. Keywords: Lecturers; Teacher;, Homestay; Perception; Educational Tourism